Importance of genetic data in resolving cryptic species: A century old problem of understanding the distribution of Minervarya syhadrensis Annandale 1919, (Anura: Dicroglossidae) - Phuge, Samadhan; Patil, Ajinkya Bharatraj; Pandit, Radhakrishna; Kulkarni, Nirmal U; Chennakeshavamurthy, B.h.; Deepak, P.; Dinesh, K.p. (Zootaxa, 2020)
Frogs of the genus Minervarya are cryptic and widely distributed in South Asia. However, many of them lack information about the precise type locality, genetic data, and distribution range. The present study aimed to examine the genetic affinities of a widely distributed species Minervarya syhadrensis around its type locality in the northern Western Ghats (Pune, Maharashtra). We studied the type specimen of M. syhadrensis and collected similar sized Minervarya frogs from Pune district. In the field, we observed two different calls from morphologically similar (M. syhadrensis like) males suggesting the sympatric occurrence of two cryptic species (that we initially named Minervarya species A and Minervarya species B). We analyzed morphology, call pattern, and mitochondrial 16S rRNA gene sequence of both species. Minervarya species A has a long call with a low pulse repetition rate and higher dominant frequency compared to that of the Minervarya species B. These species cannot be differentiated based on morphometric data. However, they can be sorted out using morphological characters such as the presence of longitudinal skin folds on the dorsal side (Minervarya species A) and differences in foot webbing. DNA sequences of Minervarya species A and Minervarya species B are matching with those of M. caperata and M. agricola respectively. After studying the type specimens of M. syhadrensis and M. caperata, we found morphological similarities (longitudinal skin folds) with the samples of Minervarya species A collected during the present study. Based on the results of our study (morphology and genetic) and available literature, we propose to redefine M. syhadrensis as applying to the lineage initially named Minervarya species A, and to treat the species M. caperata as a junior synonym of M. syhadrensis. Our study will be helpful in further taxonomic revision of the genus, and provides natural history information for M. syhadrensis and M. agricola.